Racial and Ethnic Disparities in Provider-Related Barriers to Health Care for Children in California After the ACA. (February 2019) - Alberto, Cinthya K.; Kemmick Pintor, Jessie; McKenna, Ryan M.; Roby, Dylan H.; Ortega, Alexander N.
The aim of this study was to examine disparities in provider-related barriers to health care by race and ethnicity of children in California after the implementation of the Affordable Care Act (ACA). California Health Interview Survey child (0-11 years) survey data from 2014 to 2016 were used to conduct multivariable logistic regressions to estimate the odds of reporting any provider-related barrier, trouble finding a doctor, child's health insurance not accepted by provider, and child not being accepted as a new patient. Compared with parents of non-Latino white children, parents of non-Latino black, Latino, Asian, and other/multiracial children were not more likely to report experiencing any of the 4 provider-related barrier measures. The associations between children's race and ethnicity and parents' reports of provider-related barriers were nonsignificant. Findings demonstrate that there are no significant racial/ethnic differences in provider-related barriers to health care for children in California in the post-ACA era.